Retrospective Study of Oral Lichen Planus and Oral Lichenoid Lesions: Clinical Profile and Malignant Transformation - Shahla Kakoei; Molook Torabi parizi; Maryam Rad; Nahid Karbasi; Sahar Mafi (Shiraz University of Medical Sciences, 2022)
Statement of the Problem: Oral lichen planus (OLP) and other oral lichenoid lesions (OLL) are reported to have the potential of malignant transformation and dysplastic changes, turning into oral squamous cell carcinoma (SCC). While the world health organization (WHO) has classified OLP as a precancerous lesion of the oral cavity, there is still much debate among researchers about its risks and malignancy potential.  Purpose: The present study aimed to determine malignant transformation in OLP and OLL and understand related risk factors. Materials and Method: This retrospective study was performed on 356 patients of the Oral Medicine Department of Dental School of Kerman Medical University from 1998 to 2020. All patients' records were gathered. In addition, patients were followed up routinely. Second biopsy was taken as needed. The samples, previously taken from the patients, were re-evaluated according to WHO histopathologic criteria for diagnosing OLP, OLL, dysplasia, and SCC by an experienced pathologist and compared with first reports. Results: Dysplastic changes were observed in 6.2% of the patients. In more than half of the patients, dysplastic changes were present right from the start and 2.20% of the patients had experienced dysplastic changes averagely within 2.05 years of the onset of lesions. Multiple logistic regression showed that the risk of dysplasia increases with aging (p= 0.013), smoking (p= 0.0001), and thyroid disorders (p= 0.008). Conclusion: Given the rather high prevalence of oral lichen planus and lichenoid lesions, further research appears to be needed to determine the etiology of these lesions, malignant transformations, and the factors affecting this probability. Considering the findings, it is imperative to meticulously record the information of all patients with oral lichen planus and lichenoid lesions in the initial examinations as well as close follow-ups and employ diagnostic tools such as toluidine blue staining or even repeat biopsy when necessary.